Zarządzanie strategiczne w małych przedsiębiorstwach województwa dolnośląskiego - Sołoducho-Pelc, Letycja (Strategic management in small firms in Lower Silesia, 2006)
This paper is an attempt of presenting research results regarding strategic management in small firms in Lower Silesia. The author describes how these small firms deal with different steps in the strategic management process and discusses the reasons why they diverge from the theoretical process. This research included such aspects of strategic management like: the process of creating strategy, time horizon and the main strategic fields, strategic analysis, types of strategies and their feasibility.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 288-300